The efficacy and safety of quinagolide in hyperprolactinemia treatment: A systematic review and meta-analysis - Zeng, Yanyang; Huang, Qingliang; Zou, Yunzhi; Tan, Jiacong; Zhou, Wu; Li, Meihua (Frontiers in Endocrinology, 2023)
Purpose Three dopamine agonists [bromocriptine, cabergoline, and quinagolide (CV)] have been used for hyperprolactinemia treatment for decades. Several studies have reviewed the efficacy and safety of bromocriptine and cabergoline. However, no systematic review or meta-analysis has discussed the efficacy and safety of CV in hyperprolactinemia and prolactinoma treatment. Methods Five medical databases (PubMed, Web of Science, Embase, Scopus, and Cochrane Library) were searched up to 9 May 2022 to identify studies related to CV and hyperprolactinemia. A meta-analysis was implemented by using a forest plot, funnel plot, sensitivity analysis, meta-regression, and Egger’s test via software R 4.0 and STATA 12. Results A total of 1,211 studies were retrieved from the five medical databases, and 33 studies consisting of 827 patients were finally included in the analysis. The pooled proportions of patients with prolactin concentration normalization and tumor reduction (>50%) under CV treatment were 69% and 20%, respectively, with 95% confidence intervals of 61%–76% and 15%–28%, respectively. The pooled proportion of adverse effects was 13%, with a 95% confidence interval of 11%–16%. Conclusion Our study showed that CV is not less effective than cabergoline and bromocriptine in treating hyperprolactinemia, and the side effects were not significant. Hence, this drug could be considered an alternative first-line or rescue treatment in treating hyperprolactinemia in the future. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022347750.